Reduced T cell immunity in unmedicated, comorbidity-free obsessive-compulsive disorder: An immunophenotyping study. (May 2021) - Subbanna, Manjula; Shivakumar, Venkataram; Jose, Dania; Venkataswamy, Manjunath; Debnath, Monojit; Ravi, Vasanthapuram; Reddy, Y.C. Janardhan; Venkatasubramanian, Ganesan; Narayanaswamy, Janardhanan C.
Abstract: Background: Immune system aberrations have been postulated to play a role in the pathophysiology of Obsessive-compulsive disorder (OCD). This study was aimed to examine the profile of immune cell subsets in peripheral blood of un-medicated OCD patients. Method: Thirteen drug-naïve/free OCD patients and twenty-six age & sex matched healthy controls were recruited. Immunophenotyping was carried out by staining the whole blood specimens with fluorescent monoclonal antibodies against the cell surface markers such as CD45, CD3, CD16, CD56, CD8, CD4, CD28, CD25 and CD127, followed by data acquisition on BD FACSVerse™ flow cytometer. The proportions of CD4 and CD8 T cells; T regulatory (Tregs), Natural Killer (NK) cells and NK-T cells were compared between patients with OCD and healthy control subjects. Results: Significantly reduced percentage of T regulatory (Treg) cells was observed in individuals with OCD compared to healthy control subjects [1.0 ± 0.7 vs. 1.9 ± 1.4; p = 0.03, r = 0.33]. Conclusion: Treg cells play a crucial role in regulating the immune response, especially by suppressing the functional activities of T cells. In this study, decreased population of Treg cells essentially indicates a dysregulated T cell and/or T cell mediated immune activation in drug-naïve OCD patients. This preliminary observation might form the basis of further studies examining the immuno-inflammatory/autoimmune origin of OCD. Highlights: Immune system aberrations play a significant role in the pathophysiology of Obsessive-compulsive disorder. T-regulatory cells play a crucial role in regulating the immune response by suppressing the functional activities of T cells. T-regulatory cell population essentially indicates a dysregulated T cell and/or T cell mediated immune activation.